Pengaturan Penyelesaian Sengketa Penanaman Modal dalam Peraturan Daerah Nomor 7 Tahun 2018 tentang Penanaman Modal Provinsi Riau - Deliana, Evi (SASI, 2020)
Investment is any form of investment activity, both by domestic investors and foreign investors to do business in the territory of the Republic of Indonesia. Riau Province has issued Regional Regulation No. 7 of 2018 concerning Investment in Riau Province (PMPR). But there are weaknesses and disharmony with the higher regulation, the 2007 Investment Act. The research method used is normative legal research. The regulation in the PMPR regulation is still unclear, especially if there is an obligation to resolve disputes that occur between the government and foreign investors through national arbitration. Whereas in accordance with the 2007 Investment Act, dispute resolution between the government and foreign investors is carried out through international arbitration institutions based on the agreement of the parties.